Benzyl Acetate: A Review on Synthetic Methods - Zainab Esmail Sadeq; Noor Sabah Al-Obaidi; Omar G. Hammoodi; Ahmed N. Abd; Anfal Salam Al-Mahdawi (Genius Journals, 2022)
Synthetic methods of benzyl acetate using different catalysts such as strong acid cation exchange resin, Palladium, Benzyl trialkylammonium, Polyaniline, Sb-Pd-TiO2, Pd,Sb/TiO2, Bronsted acidic ionic liquid, H2SO4(NH4)2 Ce (PO4)2 .H2O, SiW12/SiO2, Ni/SiO2, (NH4)6{Mo9O32}.8H2O, Micro/Meso – HZSM – 5, Lipase Immobilized, 1-methyl-3-(3- sulfopropyl) imidazolium tungstophosphate, salt / glycerol all these catalysts have been reviewed and studied. The catalysts that used in preparation of benzyl acetate improved the some properties such as yield, temperature and reaction time of benzyl acetate. These techniques benefit from simple procedures and minimal investment costs.
Keywords: Esters; synthetic methods; catalysts